First-principles study on the structural, elastic and electronic properties of Ti2SiN under high pressure. (July 2016) - Li, Hui; Wang, Zhenjun; Sun, Guodong; Yu, Pengfei; Zhang, Wenxue
Abstract: The structural, elastic and electronic properties of Ti2 SiN under pressure range of 0–50 GPa have been systemically investigated by first-principles calculations. It is found that both Poisson׳s ratio and shear anisotropy factor of Ti2 SiN increase with pressure, and Ti2 SiN is elastic anisotropic. The DOS and Mulliken population analysis have been explored, which indicts that Ti2 SiN is metallic–covalent–ionic in nature. The present calculations may contribute preliminary results and a better understanding of Ti2 SiN for its applications under high pressure environments. Highlights: Structural, elastic and electronic properties of Ti2 SiN under pressure are reported. Both Poisson׳s ratio and shear anisotropy factor increase with pressure. Ti2 SiN is elastic anisotropic and metallic–covalent–ionic in nature.